A scaling law for monocrystalline PV/T modules with CCPC and comparison with triple junction PV cells. (15th September 2017) - Li, W.; Paul, M.C.; Rolley, M.; Sweet, T.; Gao, M.; Siviter, J.; Montecucco, A.; Knox, A.R.; Baig, H.; Mallick, T.K.; Fernandez, E.F.; Han, G.; et al.
Highlights: A scaling law is developed for monocrystalline PV modules with and without CCPC. Model and method for establishing the law are validated. CCPCs affect significantly the law for monocrystalline PV cells. The law is applied to predict the performance of PV/thermal modules with CCPC. Abstract: Scaling laws serve as a tool to convert the five parameters in a lumped one-diode electrical model of a photovoltaic (PV) cell/module/panel under indoor standard test conditions (STC) into the parameters under any outdoor conditions. By using the transformed parameters, a current-voltage curve can be established under any outdoor conditions to predict the PV cell/module/panel performance. A scaling law is developed for PV modules with and without crossed compound parabolic concentrator (CCPC) based on the experimental current-voltage curves of six flat monocrystalline PV modules collected from literature at variable irradiances and cell temperatures by using nonlinear least squares method. Experiments are performed to validate the model and method on a monocrystalline PV cell at various irradiances and cell temperatures. The proposed scaling law is compared with the existing one, and the former exhibits a much better accuracy when the cell temperature is higher than 40 °C. The scaling law of a triple junction flat PV cell is also compared with that of the monocrystalline cell and the CCPC effects on the scaling law are investigated with the monocrystalline PV cell. It is identified that the CCPCs impose a more significant influence on the scaling law for the monocrystalline PV cell in comparison with the triple junction PV cell. The proposed scaling law is applied to predict the electrical performance of PV/thermal modules with CCPC.